Development of Social Skill Rating Scale for Primary School Students-Teacher Form (SSRS-T) and Analysis of its Psychometric Properties. (25th July 2015) - Karatas, Zeynep; Sag, Ramazan; Arslan, Derya
Abstract: The aim of the study is to develop a new scale, called the "Social Skills Rating Scale for Primary School Students-Teacher Form" (SSRS-T). This study was carried out on four different groups consisting of primary school students from Burdur in Turkey. The psychometric properties of the Scale (SSRS-T) were analyzed by means of item analysis, exploratory factor analysis, the first level of the confirmatory factor analysis (CFA) and internal consistency and test-retest methods. The exploratory factor analysis (EFA) results demonstrated that the scale comprised two factors. As a result of the EFA, the factor loadings of 24 items in the two factors were found to vary between 0.61 and 0.84. These two factors explained 64% of the total variance. CFA results demonstrated that two dimensional model provides good fit as per obtained fit index values. The Scale (SSRS-T)'s internal consistency coefficient and test-retest reliability coefficient were each determined to be 0.97 and 0.87. In conclusion, Social Skills Rating Scale for Primary School Students can be used as a reliable and valid measure for Turkish primary school students.